PENGARUH PELATIHAN DAN DISIPLIN TERHADAP KINERJA KARYAWAN PADA PT KINCO PRIMA - Willson, Charles; Hikmah, Hikmah (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
This research has goal to know the Influence of training and discipline towards employee’s performance at kinco prima incorporate. Data population in this research is all members of workers on those company with a numbers of 107 respondents as a sample. On this research, tested variables consist of training and discipline as independent variables, and employee’s performance as a dependent variable. The result of these research shown that training  has significantly impact at the significance level 0,001 it mean that, first hypothesis in this research was proven, accepted. Meantime the result shown by discipline, this variable has significantly impact toward employee’s performance, at the significance level 0.000, it mean secondary hypothesis in this research was  proven, or accepted. And for the third hypotheses, training and discipline have significantly impact toward employee’s performance at the level of significance 0.000, it shown that third hypotheses, accepted. In this research adjusted R2, at the level of 0.665, it means that employee’s performance could be explained by training and discipline variables at the level 66.5%, and the rest 33.5% was influenced by others variables excluded this research.  Kata kunci : Training, discipline and employee’s performance